Clinical, biochemical, and genetic distinctions in patients with mitochondrial involvement versus other genetic disorders - SECU, Doina; BLANITA, Daniela; USURELU, Natalia; SACARA, Victoria (One Health & Risk Management, 2025)
Introduction. Mitochondrial diseases are clinically and genetically heterogeneous disorders characterized by respiratory chain dysfunction, often mimicking other multisystem genetic conditions, necessitating an integrated clinical, biochemical, and molecular diagnosis. This study aims to compare the clinical, biochemical, and genetic profiles of patients with mitochondrial involvement and those with other inherited genetic disorders.Material and methods. We analyzed 81 patients with suspected mitochondrial disease (Nijmegen Mitochondrial Disease Score ≥3), categorized into Group 1 (mitochondrial involvement) and Group 2 (other inherited disorders). Clinical, biochemical, instrumental, and molecular evaluations were performed using qPCR-HRM and Sanger sequencing, with data analyzed through descriptive statistics and non-parametric tests.Results. Group 1 showed significantly higher rates of severe neuromuscular impairment, skill regression, ocular abnormalities, elevated plasma lactate and alanine, and characteristic neuroimaging findings, including basal ganglia abnormalities and cerebral-cerebellar atrophy. Genetic analysis identified phenotype-associated mutations in 32 patients, primarily affecting Complex I and V subunits and mitochondrial RNA genes, often involving multiple respiratory chain sites. Group 2 comprised a range of genetically confirmed non-mitochondrial disorders, identified through targeted genomic testing.Conclusions. This study highlights the crucial role of integrated clinical, biochemical, and genomic approaches, emphasizing the importance of comprehensive molecular testing and multidisciplinary evaluation in addressing the diagnostic complexities of overlapping genetic disorders.